2023
DOI: 10.1002/solr.202300214
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered PbI2 with Post‐Processing for Perovskite Solar Cells

Abstract: Conformal deposition of perovskite films on textured silicon surfaces using a dry process is crucial for producing high‐performance perovskite/silicon tandem solar cells. Herein, a radio frequency magnetron sputtering process is used with a PbI2 target to deposit precursor films. Iodination, thermal annealing, and dimethyl sulfoxide treatment are employed as posttreatment processes to improve the stoichiometry, crystallinity, and surface morphology of the PbI2 precursor. The precursor films are converted into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…These indexes were in good agreement with the literature and theoretically calculated values with tetragonal phases of MAPbI 3 . 12,17,26) The patterns also revealed that the (110) peak became broader with lower intensities, which could result from lattice-distortion of MAPbI 3 from the transformation to fibrous interconnected grain.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…These indexes were in good agreement with the literature and theoretically calculated values with tetragonal phases of MAPbI 3 . 12,17,26) The patterns also revealed that the (110) peak became broader with lower intensities, which could result from lattice-distortion of MAPbI 3 from the transformation to fibrous interconnected grain.…”
mentioning
confidence: 97%
“…[5][6][7][8][9] Among the fabrication processes, RF sputtering provides outstanding advantages in terms of precise film formation, high uniformity, and structural control. [10][11][12] In addition, the crystal structure of sputtered films could be controlled according to the Thornton structural zone model, which determines the grain size, orientation, and morphology of sputtered films as a function of the given specific pressure and substrate temperature. [13][14][15] This level of control is critical for tailoring the optical, electrical, and functional properties of the film for various device applications.…”
mentioning
confidence: 99%